2005
DOI: 10.1080/01650250500147402
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of child temperament and parenting in Beijing, China and the western United States

Abstract: The purpose of this investigation was to examine comparable dimensions and linkages between child temperament and parenting styles with samples from Beijing, China and the western United States. Participants included 404 mothers and fathers from Beijing, China and 325 mothers and fathers from the western United States. Both mothers and fathers completed Buss and Plomin's (1984) EAS Temperament Scale as well as a spousal-report measure of parenting styles. Structural equation modelling was used to identify inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 25 publications
5
64
0
4
Order By: Relevance
“…As one of the first longitudinal studies on parenting, temperament, and Chinese children's behavior problems (e.g., Chen, Liu, & Li, 2000;Chen et al, 2002), this study extended the previous research with this population (which was mostly cross-sectional and/or did not simultaneously include both parenting and temperament as predictors of adjustment, e.g., Chen et al, 2002;Eisenberg et al, 2007;Nelson et al, 2006;Porter et al, 2005). The most important findings are the prospective and unique relations of authoritative and authoritarian parenting and temperamental anger/frustration to Chinese children's externalizing problems, which provided evidence for the generalization of socialization and temperament models for externalizing problems to the Chinese culture.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…As one of the first longitudinal studies on parenting, temperament, and Chinese children's behavior problems (e.g., Chen, Liu, & Li, 2000;Chen et al, 2002), this study extended the previous research with this population (which was mostly cross-sectional and/or did not simultaneously include both parenting and temperament as predictors of adjustment, e.g., Chen et al, 2002;Eisenberg et al, 2007;Nelson et al, 2006;Porter et al, 2005). The most important findings are the prospective and unique relations of authoritative and authoritarian parenting and temperamental anger/frustration to Chinese children's externalizing problems, which provided evidence for the generalization of socialization and temperament models for externalizing problems to the Chinese culture.…”
Section: Discussionsupporting
confidence: 59%
“…Chao (1994Chao ( ,2001 proposed that authoritative and authoritarian parenting may not fully capture the important features of Chinese parenting and that an indigenous construct such as "guan" or training should be considered. Nonetheless, recent empirical investigations suggest that both the attributes of authoritative (especially warm and responsive) and authoritarian (especially coercive/punitive) parenting and their relations to Chinese children's adjustment are similar to those found in the Euro-American culture (e.g., Chang, Lansford, Schwartz, & Farver, 2004;Chen, Wang, Chen, & Liu, 2002;Nelson, Hart, Yang, Olsen, & Jin, 2006;Porter et al, 2005;Sorkhabi, 2005;Zhou, Eisenberg, Wang, & Reiser, 2004). Moreover, Chinese parents' ratings of guan are moderately and positively correlated with warmth (Stewart et al, 1998), suggesting that the indigenous notion of guan might be consistent with authoritative parenting (Nelson et al, 2006).…”
Section: Generalizability Of the Model To Chinese Familiesmentioning
confidence: 99%
“…'I state punishments to our child and do not actually do them' and 'I find it difficult to discipline our child'). The PDSQ has been shown to be reliable and valid among preschool and school-aged children (39) . On the original shortened version, internal consistencies for the two parenting styles, authoritarian and permissive, were 0?82 and 0?64, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Cohen (2001) suggests "play is one of the best ways to engage with children, pulling them out of emotional shutdown or misbehaviour, to a place of connection and confidence" (p. 16). Overall children who are more adaptable, sociable, and soothable have often experienced warm and responsive parenting whereas difficult children are more likely to have experienced less responsive parenting (Fish et al, 2007;Haskett & Willoughby, 2006;Hunt, 2001;Porter et al, 2005).…”
Section: Parenting Stylesmentioning
confidence: 99%
“…Studies have shown that this type of parenting is ineffective. Authoritarian parenting can be described as parenting involving over control, unfair or harsh discipline, and inflexible enforcement of rules (Baydar, Reid & Webster-Stratton, 2003;De Vito & Hopkins, 2001;Porter et al, 2005;Xu et al, 2005). People practicing an authoritarian parenting style are more likely to use power-assertive behaviour, including yelling and grabbing, with their children (DeVito & Hopkins, 2001).…”
Section: Parenting Stylesmentioning
confidence: 99%